(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2016)
Background. Stress and Anxiety are commonly observed before major surgical procedures, such as heart surgical operations. Aim of the current study is to investigate the effect of the preoperative anaesthesiological interview on these parameters. Methods. We prospectively included in the study 152 patients planned to undergo elective heart surgery. All patients were examined with the State-Trait anxiety inventory (STAI) scale on admission and again before surgery (prior to the anaesthesiological interview for the control group and after the latter for the intervention group). Results. Members of the control group had significantly higher levels of stress based on the test results, on the day prior to surgery. On the contrary, the members of the intervention group had significantly lower levels of stress on the same day. Conclusions. The anaesthesiological interview has a positive influence as it lowers the preoperative levels of stress and anxiety.Â